2010
DOI: 10.1111/j.1600-051x.2010.01689.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic position, smoking, and plaque: a pathway to severe chronic periodontitis

Abstract: This study presented a potential explanatory pathway for the relationship between SEP and SCP. Low level of education was proposed as a distal determinant, leading to tobacco smoking and higher levels of plaque, and finally to SCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
6
33
0
Order By: Relevance
“…These results are also consistent in the literature, as lower occurrence rates of periodontal diseases are found in those with higher education . Inappropriate oral hygiene, mainly evidenced by higher levels of biofilm accumulation, are found in lower education individuals …”
Section: Discussionsupporting
confidence: 91%
“…These results are also consistent in the literature, as lower occurrence rates of periodontal diseases are found in those with higher education . Inappropriate oral hygiene, mainly evidenced by higher levels of biofilm accumulation, are found in lower education individuals …”
Section: Discussionsupporting
confidence: 91%
“…Tobacco smoking exerts a substantial destructive effect on the periodontal tissues and increases the rate of periodontal disease progression [24]. Risk factors including tobacco smoking modify the host response to the challenge of bacteria in microbial dental plaque [25, 26].…”
Section: Risk Factors Of Periodontal Diseasementioning
confidence: 99%
“…Indirect mechanisms include the link between education and the two main risk factors for chronic periodontitis: smoking [52] and diabetes type 2 [53]. Lower educational attainment, which is a close correlate of IQ, may also directly lead to poorer coping strategies [54], higher BMI [55], lower levels of dental services use [56], low degree of periodontal health awareness [57], and irregular oral self-care practices [58], that in themselves are linked to poor oral hygiene habits may lead to higher levels of dental plaque [59]. Only one study which met our criteria of inclusion showed a significant decrease of the risk to develop chronic periodontitis in the low educated subgroup after adjustment for oral health behaviors [32].…”
Section: Discussionmentioning
confidence: 99%